(untitled) (Biological Sciences - PJSIR, 1996)
The acid dissociation constant of benzaldehyde-Z-hydroxyazine (H2A) is determined spectrophotometrically in a series of universal buffer solutions (20% ethanol, v/v) of varying pH. Cu (II), Co (II) and Ni (II) omplexes of H2A have been prepared and characterized by elemental analysis, molar conductance, electronic and infrared spectra measurements. It is concluded that the ligand acts as bivalent ONNO tetradentate, The complexes are suggested to exhibit a distorted octahedral geometry.